News flow and REIT returns: evidence from Singapore - Chakravarty Diya (Nanyang Technological University, 2024)
This study aims to contribute to the field of REITs literature by understanding the impact that newspapers have on price returns. While existing literature studies the spillover effects of information flow on asset classes like equity, bonds, commodity futures and even Bitcoins, there exists very limited research which attempts to understand how news impacts REIT prices on a monthly level. Additionally, there is a lack of study of the impact of information flow on the Asian REITs market, and this study aims to add value to this region. This study takes the 2 main newspapers in Singapore, namely Straits Times and Business Times to create monthly count indices of the topics created through a machine learning algorithm LDA. Subsequently a VAR analysis is conducted using the relevant monthly count indices on the benchmark Singapore REIT Index, the S&P 500 Singapore REIT. The results indicated the lagged impact of the S-REIT returns on the current return, but failed to reject any insignificance with the monthly count indices of any of the topics. It was concluded that a monthly lag of the underlying topics does not have any significant impact in the causality of the current S-REIT returns.